NILAI MORAL TRI HITA KARANA DALAM ALBUM “KERAMAT” CIPTAAN H. RHOMA IRAMA - Harefa, Darmawan; I Made Sutajaya; I Wayan Suja; Ida Bagus Made Astawa (LPPM Universitas Nias Raya, 2024)
The purpose of this study is to characterize Tri Hita Karana's moral principles as they appear in the H. Rhoma Irama album